The Impact of Pre-Marriage Counseling on The Thinking Patterns of Students at Tunas Bangsa Vocational School in Choosing A Prospective Wife - Roni Hidayat; Baiq Ratna Mulhimah; Lalu Muhammad Nurul Wathani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Islam is a perfect religion that governs all aspects of life, including choosing a spouse and determining the right time to marry. However, given the high divorce rate in Indonesia, particularly in Jember, as indicated by data from the Central Statistics Agency at the beginning of 2023, where 6,000 residents of Jember filed for divorce, this signifies the unpreparedness of married couples regarding their rights and obligations in fulfilling their duties. This situation serves as the basis for conducting pre-marriage counseling at SMK Tunas Bangsa regarding determining the appropriate time to marry. Pre-marriage counseling involves systematic guidance and support to help students understand the best time to start a family and build confidence in preparing systematically for marriage if they wish to proceed. This study was conducted using a pre-experimental method with a one-group pretest-posttest design, involving a pretest, followed by counseling, and then a posttest. The results of the counseling showed an increase in students' knowledge regarding tips for finding the right partner for marriage according to Islamic perspectives.